Burden of Future Liver Abnormalities in Patients With Intrahepatic Cholestasis of Pregnancy. (13th March 2021) - Monrose, Erica; Bui, Anthony; Rosenbluth, Emma; Dickstein, Daniel; Acheampong, Derrick; Sigel, Keith; Ferrara, Lauren; Kushner, Tatyana
Abstract : INTRODUCTION: There are limited data on the incidence, predictors, and time to future liver abnormalities in patients with intrahepatic cholestasis of pregnancy (ICP). METHODS: Single-center retrospective study of pregnant women with and without ICP who delivered from 2005 to 2009 evaluating incidence and time to future liver abnormalities. Women returning for care with liver function tests at a minimum of 6 months postpartum were included. Liver disease diagnoses and liver functions test abnormalities were compared. Time to development of alanine aminotransferase (ALT) >25 U/L, alkaline phosphatase (ALP) >140 U/L, and diagnosis of liver disease (through imaging or clinical evaluation) were compared between women with and without ICP using Kaplan-Meier methods and Cox regression models. RESULTS: A total of 255 women with ICP and 131 age-matched control subjects with delivery during the same period were identified. Subjects in both groups were similar in follow-up time, age at pregnancy, prepregnancy body mass index, and ethnicity (≥75% were Hispanic in both groups). On univariate analyses, ICP was associated with increased incidence of ALT >25 U/L P < 0.01 ALP >140 U/L ( P < 0.01) and liver disease ( P = 0.03). Adjusting for metabolic factors, ICP diagnosis was associated with risk of future liver abnormalities: postpartum ALT >25 U/L (hazard ratio [HR] 1.9, P < 0.01), ALP >140 U/L (HR 3.4, P < 0.01), and liver disease (HR 1.5, P = 0.05). DISCUSSION: In our cohort of urban women, ICP diagnosis predicted risk of future liver disease and abnormal liver tests. Women with pregnancies complicated by ICP may benefit from surveillance for postpartum liver abnormalities.